Cellular localisation of HHV-8 in Castleman's disease: is there a link with lymph node vascularity?. Issue 2 (1st April 2000) - O'Leary, J; Kennedy, M; Howells, D; Silva, I; Uhlmann, V; Luttich, K; Biddolph, S; Lucas, S; Russell, J; Bermingham, N; O'Donovan, M; Ring, M; et al.
Abstract : Aims —Human herpesvirus 8 (HHV-8) has been identified in multicentric Castleman's disease and in angioimmunoblastic lymphadenopathies. However, the presence of the virus does not necessarily indicate an aetiological role in these conditions. This study investigates the cell types infected by HHV-8 in Castleman's disease and examines the correlation between HHV-8 and Castleman's disease lymph node angiogenesis. Methods —Sixteen formalin fixed, paraffin wax embedded samples from patients with Castleman's disease (six multicentric, 10 solitary) were examined for the presence of HHV-8 using the polymerase chain reaction (PCR), non-isotopic in situ hybridisation, PCR in situ hybridisation (PCR-ISH), and real time quantitative TaqMan PCR to HHV-8 open reading frame 26 (ORF-26), and viral (v)-cyclin encoding regions. Vascularity was assessed using CD34, CD31, and factor VIII immunocytochemistry, and lymph nodes were scored as "low" or "high". Results —Five multicentric Castleman's disease and two solitary Castleman's disease biopsies were positive for HHV-8. HHV-8 was identified in approximately 10% of intranodal B lymphocytes, in endothelial cells, and in subcapsular spindle cell proliferations. The copy number of HHV-8 was low at 10–50 copies/1000 cells. The highest copy number was in subcapsular spindle cells. There was no correlation between vascularity score and HHV-8 status. Conclusion —The preferential localisation of HHV-8 in subcapsular spindle cell proliferations (where early intranodal Kaposi's sarcoma initiates) and endothelial cells in Castleman's disease might finally explain the link between intranodal Kaposi's sarcoma and Castleman's disease.